Analysis of seasonal variation of antibiotic prescribing for respiratory tract diagnoses in primary care practices - Lacey Serletti; Lauren Dutcher; Kathleen O. Degnan; Julia E. Szymczak; Valerie Cluzet; Michael Z. David; Leigh Cressman; Lindsay W. Glassman; Keith W. Hamilton; for The Centers for Disease Control and Prevention (CDC) (Cambridge University Press, 2023)
Abstract Objective: To determine antibiotic prescribing appropriateness for respiratory tract diagnoses (RTD) by season. Design: Retrospective cohort study. Setting: Primary care practices in a university health system. Patients: Patients who were seen at an office visit with diagnostic code for RTD. Methods: Office visits for the entire cohort were categorized based on ICD-10 codes by the likelihood that an antibiotic was indicated (tier 1: always indicated; tier 2: sometimes indicated; tier 3: rarely indicated). Medical records were reviewed for 1,200 randomly selected office visits to determine appropriateness. Based on this reference standard, metrics and prescriber characteristics associated with inappropriate antibiotic prescribing were determined. Characteristics of antibiotic prescribing were compared between winter and summer months. Results: A significantly greater proportion of RTD visits had an antibiotic prescribed in winter [20,558/51,090 (40.2%)] compared to summer months [11,728/38,537 (30.4%)][standardized difference (SD) = 0.21]. A significantly greater proportion of winter compared to summer visits was associated with tier 2 RTDs (29.4% vs 23.4%, SD = 0.14), but less tier 3 RTDs (68.4% vs 74.4%, SD = 0.13). A greater proportion of visits in winter compared to summer months had an antibiotic prescribed for tier 2 RTDs (80.2% vs 74.2%, SD = 0.14) and tier 3 RTDs (22.9% vs 16.2%, SD = 0.17). The proportion of inappropriate antibiotic prescribing was higher in winter compared to summer months (72.4% vs 62.0%, P < .01). Conclusions: Increases in antibiotic prescribing for RTD visits from summer to winter were likely driven by shifts in diagnoses as well as increases in prescribing for certain diagnoses. At least some of this increased prescribing was inappropriate.